2005
DOI: 10.4049/jimmunol.175.6.3971
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Thymus-Dependent Responses by Murine Dendritic Cells Infected with Foot-and-Mouth Disease Virus

Abstract: Foot-and-mouth disease virus (FMDV) is a cytopathic virus that experimentally infects mice, inducing a thymus-independent neutralizing Ab response that rapidly clears the virus. In contrast, vaccination with UV-inactivated virus induces a typical thymus-dependent (TD) response. In this study we show that dendritic cells (DCs) are susceptible to infection with FMDV in vitro, although viral replication is abortive. Infected DCs down-regulate the expression of MHC class II and CD40 molecules and up-regulate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
44
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 48 publications
10
44
2
1
Order By: Relevance
“…A similar type of response has been described for other viruses such as vesicular stomatitis virus (VSV) (5,58). We have recently shown that during the early phase of the response against infectious FMDV, there is a transient but generalized suppression of TD responses (51). This effect is mediated, at least in part, by the downregulation of major histocompatibility complex class II and CD40 molecules on dendritic cells (DCs) and by the production of interleukin-10 (IL-10) by splenocytes (51).…”
Section: Infection Of Mice With Cytopathic Foot-and-mouth Disease Virsupporting
confidence: 62%
See 3 more Smart Citations
“…A similar type of response has been described for other viruses such as vesicular stomatitis virus (VSV) (5,58). We have recently shown that during the early phase of the response against infectious FMDV, there is a transient but generalized suppression of TD responses (51). This effect is mediated, at least in part, by the downregulation of major histocompatibility complex class II and CD40 molecules on dendritic cells (DCs) and by the production of interleukin-10 (IL-10) by splenocytes (51).…”
Section: Infection Of Mice With Cytopathic Foot-and-mouth Disease Virsupporting
confidence: 62%
“…Bone marrow-derived DCs were obtained as previously described (51). Infection of DCs was performed with FMDV serotype O1 Campos, provided by the Servicio Nacional de Sanidad y Calidad Agroalimentaria, Argentina, at a multiplicity of infection (MOI) of 10 for 4 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…UV inactivation was used to cross-link the FMDV RNA genome and prevent replication while retaining the capsid structure. The protocol used was based on that of Ostrowski et al (44) with some minor modifications. FMDV was transferred to tissue culture plates on ice to a depth of no greater than 2 mm at a distance of 10 cm from the UV source (UVP, Upland, CA).…”
mentioning
confidence: 99%